Karateristik Dan Model Kepemimpinan Kepala Sekolah SMA Negeri 1 Tanjungbalai - Hendri Irawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research delves into the characteristics and leadership models of the School Principal at SMA Negeri 1 Tanjungbalai. Using a qualitative approach, the study explores the impact of leadership on teacher performance, student discipline, and learning outcomes. Transformational Leadership Theory, Hersey-Blanchard's Situational Leadership, and Distributive Leadership are integrated to form the conceptual framework. The research population involves the School Principal, teachers, and administrative staff at SMA Negeri 1 Tanjungbalai. Through interviews, observations, and document analysis, the study details the leadership characteristics and models applied in the school. The research findings are expected to provide a holistic insight into leadership practices at SMA Negeri 1 Tanjungbalai, guiding the development of more effective leadership strategies.